Peripheral nerve regeneration using a bioresorbable silk fibroin-based artificial nerve conduit fabricated via a novel freeze–thaw process - Tomoki Matsuo; Hiroo Kimura; Takayuki Nishijima; Yasuhiro Kiyota; Taku Suzuki; Narihito Nagoshi; Shinsuke Shibata; Tomoko Shindo; Nobuko Moritoki; Makoto Sasaki; Sarara Noguchi; Yasushi Tamada; et al. (Scientific Reports)
Abstract While silk fibroin (SF) obtained from silkworm cocoons is expected to become a next-generation natural polymer, a fabrication method for SF-based artificial nerve conduits (SFCs) has not yet been established. Here, we report a bioresorbable SFC, fabricated using a novel freeze–thaw process, which ensures biosafety by avoiding any harmful chemical additives. The SFC demonstrated favorable biocompatibility (high hydrophilicity and porosity with a water content of > 90%), structural stability (stiffness, toughness, and elasticity), and biodegradability, making it an ideal candidate for nerve regeneration. We evaluated the nerve-regenerative effects of the SFC in a rat sciatic-nerve-defect model, including its motor and sensory function recovery as well as histological regeneration. We found that SFC transplantation significantly promoted functional recovery and nerve regeneration compared to silicone tubes and was almost equally effective as autologous nerve transplantation. Histological analyses indicated that vascularization and M2 macrophage recruitment were pronounced inside the SFC. These results suggest that the unique properties of the SFC further enhanced the peripheral nerve regeneration mechanism. As no SFC has been applied in clinical practice, the SFC reported herein may be a promising candidate for repairing extensive peripheral nerve defects.